Effect Of Benefits, Convenience, Security, And Features Services To Student Interest In Use Of Funds As E-Wallet - Panggabean, Dewi Febryanti; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to confirm the use of an electronic wallet (also known as an